A case of anticoagulant treatment-resistant Trousseau syndrome controlled by treatment of the underlying lung adenocarcinoma: Utility of monitoring D-dimer levels. Issue 2 (February 2017) - Kuwahata, So; Takenaka, Toshihiro; Yasuda, Shunsuke; Sakoda, Takashi; Taniyama, Hiroki; Nagata, Yukitaka; Iwakawa, Jun; Matsumoto, Shuji; Seto, Takashi; Takenoyama, Mitsuhiro; Abe, Satoshi; Ohishi, Mitsuru
Abstract: We report herein a 70-year-old woman, with repeated thromboembolic events, including three cerebral embolisms and two venous thromboembolisms, despite adequate anticoagulant therapy. Trousseau syndrome was suspected, and she was diagnosed as having lung adenocarcinoma. Chemoradiotherapy was started, achieving improvements in the lung cancer, and thrombosis was also brought under control. Ten months later, the lung cancer relapsed, and second-line chemotherapy was performed. D-dimer levels, which had normalized after the first-line therapy, increased together with the relapse, but became negative again following the chemotherapy. In general, the prognosis of Trousseau syndrome is diverse. However, in this case, the course was good following the second lung cancer therapy: D-dimer levels did not increase, and there were no recurrences of thromboembolism. This experience reminds us the prognosis is most affected by whether the underlying disease is being effectively treated, and suggests that for Trousseau syndrome, despite adequate anticoagulant therapy, elevation of D-dimer levels should consider the recurrent cancer. <Learning objective: We report herein a case with repeated thromboembolic events as a result of Trousseau syndrome due to lung cancer. Chemotherapy achieved improvements, but the cancer relapsed and second-line chemotherapy was done. D-dimer levels, which had normalized, increased with the relapse before again becoming negative. This experience reminds us that prognosis is affected by treating underlying disease and suggests that elevation of D-dimer levels should consider the cancer recurrence.>